Adenomyosis in mice resulting from mechanically or thermally induced endometrial–myometrial interface disruption and its possible prevention. Issue 5 (November 2020) - Hao, Meihua; Liu, Xishi; Guo, Sun-Wei
Highlights: Mechanically and thermally induced EMID causes adenomyosis Mechanical EMID confers a higher risk of developing adenomyosis than thermal EMID The risk of developing adenomyosis seems to be related to the extent of damage Perioperative NK1R inhibitor and β-blocker may reduce the risk of adenomyosis Abstract: Research question: Do uterine procedures potentially disrupting the endometrial–myometrial interface (EMI) induce adenomyosis? Design: Six prospective, randomized controlled experiments were conducted involving a total of 106 female BALB/c and 12 female C57BL/6 mice. The incidence of adenomyosis was evaluated in these two strains of mouse after mechanically induced EMI disruption (EMID), or thermally induced EMID using electrocoagulation of different intensities. Finally, the incidence was evaluated in mice that had received perioperative administration of aprepitant (an NK1R inhibitor), propranolol (a beta-blocker) or vehicle. Body weight, hot plate latency and grade of myometrial infiltration were evaluated. Histology, immunohistochemistry and histochemistry analyses were also performed. Results: Mechanical injury to the EMI caused EMID. Adenomyosis developed in the majority of mice in the EMID groups 3 months after mechanically induced EMID but did not develop in the control group (83.3% in C57BL/6 mice, P = 0.015; 100% in BALB/c mice, P = 0.0002). With thermally induced EMID, adenomyosis was found in 30% of the EMID mice 10 weeks later, but the incidence increased to 66.7% if the extent of EMID damage was increased. In mice with perioperative administration of aprepitant or propranolol, the incidence of adenomyosis was reduced from 100% to 58.3% (both P = 0.00034). Conclusions: This study provides the first piece of experimental evidence that EMID resulting from iatrogenic uterine procedures can substantially increase the risk of developing adenomyosis, with the risk in proportion to the severity of disruption. More intriguingly, perioperative administration of an NK1R antagonist or beta-blocker significantly reduced the risk of developing adenomyosis.